Status of Cardiovascular Health in Chinese Adults - Bi, Yufang; Jiang, Yong; He, Jiang; Xu, Yu; Wang, Limin; Xu, Min; Zhang, Mei; Li, Yichong; Wang, Tiange; Dai, Meng; Lu, Jieli; Li, Mian; et al. (Journal of the American College of Cardiology, 2015)
Cardiovascular disease has become the leading cause of death in China. The goal of this study was to evaluate the current status of cardiovascular health in Chinese adults. Cardiovascular health data were collected from a nationally representative sample of 96,121 Chinese adults age ≥20 years in 2010. Ideal cardiovascular health was defined according to the American Heart Association’s 2020 Strategic Impact Goals as follows: the simultaneous presence of 4 favorable health behaviors (ideal smoking status, ideal body mass index, physical activity at goal, and healthy dietary habits) and 4 favorable health factors (ideal smoking status, untreated total cholesterol <200 mg/dl, untreated blood pressure <120/<80 mm Hg, and untreated fasting plasma glucose <100 mg/dl) in the absence of a history of cardiovascular disease. The estimated percentage of ideal cardiovascular health was 0.2% in the general adult population in China (0.1% in men and 0.4% in women). An estimated 0.7% (0.4% in men and 1.0% in women) of Chinese adults had all 4 ideal health behaviors, and 13.5% (5.0% in men and 22.3% in women) had all 4 ideal health factors. Men most frequently had 3 to 4 ideal components, and women most commonly had 4 to 5 ideal components of the 7 cardiovascular health metrics. Ideal diet (1.6%) was the least common among all cardiovascular health metrics. Female sex and younger age were the 2 most common protective factors for cardiovascular health in Chinese adults. The percentage of ideal cardiovascular health in Chinese adults is extremely low. Both population-wide and high-risk strategies should be implemented with great effort to promote cardiovascular health in China.